Penambahan Kombinasi Ekstrak Buah Mengkudu (Morinda citrifolia l.) dan Lactobacillus acidophilus dalam Ransum Terhadap Kinerja Hati Ayam Broiler - Wahyuningsih, Ani; Suthama, Nyoman; Yunianto, Vitus Dwi; Krismiyanto, Lilik (Journal Galung Tropika, 2021)
Noni fruit extract as a phytobiotic and Lactobacillus acidophilus as a probiotic is used to maintain body health and liver function in broiler chickens. The aim of this study was to determine the effect of adding a combination of noni fruit extract and Lactobacillus acidophilus in the liver ration based on serum glutamate oxaloacetate concentration transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) and relative liver weight in broiler chickens. Research materials included 189 broiler chickens (body weight 40.98 ± 1.27 g), noni fruit extract and Lactobacillus acidophilus as treatment. A fully randomized factorial design was used for this study. The addition of noni fruit extract as the first factor with levels of A1 (0.04 per cent), A2 (0.08 per cent) and A3 (0.12 per cent) and Lactobacillus acidophilus as the second factor with levels of B1 (0 per cent), B2 (0.6 per cent) and B3 (1.2 per cent) was repeated three times each treatment. The measured parameters included the concentration of SGOT, SGPT and the relative weight of the liver in broiler chickens. The data were processed using variance analysis. The results showed that the combination of Noni fruit extract and Lactobacillus acidophilus had a significant effect (P <0.05) on SGOT, SGPT and relative liver weight. The addition of a combination of 0.12 per cent noni fruit extract and 1.2 per cent Lactobacillus acidophilus does not interfere with the performance of the liver so that it has the potential to be a natural additive to improve the health of the body and the productivity of broiler chickens.